The Implementation of STEM-PBL Learning to Enhance Students' Critical Thinking Skills - Khoirunnissa, Rahma; Suwarma, Irma Rahma; Muslim, Muslim (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
This research is motivated by the importance of having 21st century skills, one of which is critical thinking skills. However, the facts show that students' critical thinking skills have not been fully realized optimally. Based on the results of preliminary studies and literature studies show that students' critical thinking skills are in the low to medium category. This research aims to enhance students' critical thinking skills through the implementation of STEM-PBL learning in the topic of temperature and heat. The research method used is quantitative research, specifically a pre-experimental design with the One Group Pretest-Posttest Design. This study involved 36 eleventh-grade students high school as the research sample. Data collection was done through a formative test based on critical thinking skill indicators. The research results indicate that the implementation of STEM-PBL learning can enhance students' critical thinking skills with an N-gain value of 0.5, categorized as medium. The highest N-gain was achieved in the indicator of basics clarification, while the lowest was in the indicator of advance clarification. Overall, the implementation of STEM-PBL learning has a positive impact on improving students' thinking skills.